Formulation and Physical Stability of Temulawak (Curcuma xanthorhiza Roxb.) Antiaging Lotion with Natural Colorant from Strawberry Extract (Fragaria vesca L) - Muhammad Alfian; Mochamad Luqni Maulana; Muhammad Mustainin (Program Studi Farmasi Universitas Mandala Waluya, 2023)
Skin protection is needed to reduce the unwanted effects of free radicals, such as antiaging lotions. Temulawak (Curcuma xanthorhiza Roxb.) contains curcumin which has antioxidant activity with the potential to antiaging. Strawberries (Fragaria vesca L) contain anthocyanins known used as natural dyes. This study aims to determine the antioxidant activity of temulawak extract then formulated as a lotion with the addition of natural colorant from strawberries and tested for physical stability. Curcuma extraction was carried out by maceration using 70% ethanol solvent to obtain a thick extract, infundation method was used to extract a strawberry. Determination of the antioxidant activity of temulawak extract using the DPPH method is expressed by the IC50 value. The antioxidant activity of temulawak extract is included in the moderate category with an IC50 value of 144.126 ppm. Evaluation of physical quality characteristics of temulawak lotion with natural colorant strawberry included organoleptic observations, spreadability, adhesion, pH test, viscosity, emulsion stability as well as stability to temperature and humidity. The results of the study after temperature and humidity treatment showed that the temulawak lotion was in the form of semi-solid, pink in color, the spreadability values were, respectively in centimeter 7.95 ; 7.35 ; 6.8 ; 7.05 ; 5.45 ; 5.85 ; 5.25 ; and 5.5 , the adhesive values are respectively in second 0.52 ; 0.56 ; 0.46 ; 0.51 ; 0.52 ; 0.50 ; 0.82 ; and 0.48, the pH value are 7; 6; 7; 7; 7; 7; 7; and 7, the viscosity values are in Pa.S 0.017; 0.031; 0.113; 0.055; 0.352; 0.263; 0.18; and 0.324. The conclusion of this study shows best formulation stability was formulas E, F, and H.